Unveiling mismatch of RTS S AS01 and R21 Matrix M malaria vaccines haplotype among Ethiopian Plasmodium falciparum clinical isolates - Aynalem Mandefro; Alebachew Messele Kebede; Mitchel Katsvanga; Fatoumatta Cham; Eniyou Oriero; Alfred Amambua-Ngwa; Lemu Golassa (Scientific Reports)
Abstract Malaria vaccines, RTS, S/AS01 and R21/Matrix which are based on the Plasmodium falciparum circumsporozoite protein (Pfcsp) have been approved by WHO for broad use in children in Africa. However, the extensive genetic diversity of Pfcsp limited its effectiveness, as vaccine efficacy reduced against non-vaccine strains. Using Oxford Nanopore Technology, we conducted amplicon sequencing of the full-length Pfcsp gene from 96 clinical isolates collected from three health centers in Ethiopia and compared the results against a reference genome. The result showed absence of population differentiation among the Ethiopian isolates. The N-terminal region was relatively conserved, with a KLKQP motif was present across all isolates. However, mutation at position A98G and an insertion of amino acids (DGNNNNGDNGREGKDEDKR) were identified in this region. The number of NANP and NVDP repeats of the central region per haplotype ranged from 39 to 42. Additionally, the Th2R and Th3R epitopes in the C-terminal region exhibited extensive polymorphism with at least one amino acid substitution compared to the reference strains. Notably, none of the Ethiopian Pfcsp haplotypes matched the vaccine haplotype. Furthermore, haplotype network and phylogenetic tree analyses shown considerable similarity among local and global isolates. The findings of this study revealed a high Pfcsp genetic diversity highlighting the need for further studies to inform allele selection for universal or region-specific vaccine development as this may influence vaccine efficacy.